2004
DOI: 10.1038/sj.npp.1300552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serotonin Transporter Promoter Polymorphisms on Serotonin Function

Abstract: The serotonin transporter promoter polymorphism (5-HTTLPR) has been associated with vulnerability to stress-induced depressive symptoms and with the speed and rate of response to antidepressant treatment. The goal of the present study was to evaluate the association between the 5-HTTLPR and the functional response of the serotonin system as measured by the neuroendocrine and cerebral metabolic response to intravenous administration of the selective serotonin reuptake inhibitor citalopram in normal control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 72 publications
5
73
0
Order By: Relevance
“…To date, a limited number of human studies have directly considered the impact of 5-HTT genotype on measures of HPA function. These investigations found no association of 5-HTT genotype with plasma cortisol, 66,72 although Smith et al 66 observed a trend towards blunted cortisol and prolactin response to acute pharmacologic increase of serotonin in those with the s allele. Most of these investigations did not examine basal levels, and were conducted on small samples of younger adults, with limited power to test genotype differences.…”
Section: Serotonin Transporter Polymorphism Memory and Hippocampal Vmentioning
confidence: 90%
See 1 more Smart Citation
“…To date, a limited number of human studies have directly considered the impact of 5-HTT genotype on measures of HPA function. These investigations found no association of 5-HTT genotype with plasma cortisol, 66,72 although Smith et al 66 observed a trend towards blunted cortisol and prolactin response to acute pharmacologic increase of serotonin in those with the s allele. Most of these investigations did not examine basal levels, and were conducted on small samples of younger adults, with limited power to test genotype differences.…”
Section: Serotonin Transporter Polymorphism Memory and Hippocampal Vmentioning
confidence: 90%
“…Others argue that s allele status confers increased vulnerability to a range of behavioral symptoms secondary to agerelated neurodegenerative processes, particularly in response to stress. 66 Thus, the phenotype associated with the 5-HTT s/l alleles may result from developmental, functional or neurodegenerative effects of the serotonin transporter polymorphism or a combination of these effects.…”
Section: Serotonin Transporter Polymorphism Memory and Hippocampal Vmentioning
confidence: 99%
“…For example, most neuroendocrine tests of central serotonergic function have shown blunted responses in s allele carriers; these include smaller prolactin increases in response to fenfluramine, clomipramine or citalopram. [86][87][88] On the other hand, the prolactin response to meta-chlorphenylpiperazine (m-CPP) was enhanced in ss homozygotes. 49 Unlike fenfluramine, clomipramine and citalopram, which act directly on the serotonin transporter to increase extracellular serotonin, the m-CPP is a postsynaptic 5-HT agonist, inducing prolactin release via its action on the 5-HT2C receptors.…”
Section: The Functionality Of 5-httlprmentioning
confidence: 99%
“…Furthermore, healthy 5-HTTLPR l/l individuals show significantly greater prolactin responses than s/s individuals after challenge with the tricyclic antidepressant clomipramine 361 or the SSRI citalopram. 362 Thus, it appears that heavy drinking, withdrawal from cocaine use and 5-HTTLPR genotype are associated with altered hormonal responses to 5-HT challenges, which may indicate SV.…”
Section: Experimental Manipulations Of 5-ht In Relation To Sv Factorsmentioning
confidence: 99%